The effectivess of MyBFF@school intervention program in reducing emotional and behavioral problems in overweight and obese secondary schoolchildren in Malaysia: a cluster randomized controlled trial - Zahari Ishak; Low Suet Fin; Wan Abdul Hakim Wan Ibrahim; Abqariyah Yahya; Fuziah Md. Zain; Rusidah Selamat; Muhammad Yazid Jalaludin; Abdul Halim Mokhtar (BMC Public Health)
Abstract Background Obesity may have negative impacts on the physical and psychosocial aspects of children. This study aimed to assess the effectiveness of the MyBFF@school intervention program on emotional and behavioral problems among overweight and obese secondary school children in Malaysia. Methods Children were assessed using the Youth Self-Report Questionnaire to measure their emotional and behavioral problems. Comparisons between the intervention group and control group after a six month intervention period were analyzed using linear mixed-effect model. Results Altogether, 768 children were recruited, 447 in the intervention and 321 in the control group. There were slight reduction in majority of YSR scales within the intervention group but there was no statistically significance different comparing intervention and control groups at baseline and at 6-months follow-up. Conclusions The findings demonstrated a feasibility of implementing a multifaceted intervention program in school children with obesity in Malaysia. More holistic and perhaps longer intervention period needed to improve the outcomes significantly among children with obesity. The findings demonstrate the importance of psychology components in intervention programs combating obesity among overweight and obese secondary school-aged children. Trial registration Clinical trial number: NCT04155255, November 7, 2019 (Retrospective registered). National Medical Research Register: NMRR-13–439-16,563. Registered July 23, 2013. The Medical Research and Ethics Committee (MREC), Ministry of Health Malaysia and Educational Planning and Research Division (EPRD), Ministry of Education Malaysia approved the intervention program. It was funded by the Ministry of Health Malaysia.